Journalism, politics and falsehood in the news during the 1930 electoral campaign in Colombia (2022)
The purpose of this article is to show the use of fear and misinformation in electoral campaigns, by the press andthe political groups associated with it; in particular, in the presidential election of 1930, which started a year early andresulted in the victory of candidate Enrique Olaya Herrera, who was supported by the Liberal Party. This campaign was special in many aspects: 1) one month before the election, the participation of a new candidate was confirmed; 2) the desperation and the failed attempts to unite the two factions existing within the conservative party; 3) the candidates’ visits to the main cities; 4) the use of new means of transport, public squares full of people and the press publishing pieces about the campaign at telegraph speed. For the above, this article emphasizes the use of fake news by politicians and journalists, who, taking advantage of the distances and rumours, created fake content to harm the image of their rivals and thus, winthe election. Content published in El Deber newspaper will be identified and classified into three categories: false connection,imposter content and invented content.